Human dental pulp stem cells cultured in serum-free supplemented medium - Bonnamain, Virginie; Thinard, Reynald; Sergent-Tanguy, Solène; Huet, Pascal; Bienvenu, Géraldine; Naveilhan, Philippe; Farges, Jean-Christophe; Alliot-Licht, Brigitte (Frontiers in Physiology, 2013)
Growing evidence show that human dental pulp stem cells (DPSCs) could provide a source of adult stem cells for the treatment of neurodegenerative pathologies. In this study, DPSCs were expanded and cultured with a protocol generally used for the culture of neural stem/progenitor cells. Methodology: DPSC cultures were established from third molars. The pulp tissue was enzymatically digested and cultured in serum-supplemented basal medium for 12 h. Adherent (ADH) and non-adherent (non-ADH) cell populations were separated according to their differential adhesion to plastic and then cultured in serum-free defined N2 medium with epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF). Both ADH and non-ADH populations were analyzed by FACS and/or PCR. Results: FACS analysis of ADH-DPSCs revealed the expression of the mesenchymal cell marker CD90, the neuronal marker CD56, the transferrin receptor CD71, and the chemokine receptor CXCR3, whereas hematopoietic stem cells markers CD45, CD133, and CD34 were not expressed. ADH-DPSCs expressed transcripts coding for the Nestin gene, whereas expression levels of genes coding for the neuronal markers β-III tubulin and NF-M, and the oligodendrocyte marker PLP-1 were donor dependent. ADH-DPSCs did not express the transcripts for GFAP, an astrocyte marker. Cells of the non-ADH population that grew as spheroids expressed Nestin, β-III tubulin, NF-M and PLP-1 transcripts. DPSCs that migrated out of the spheroids exhibited an odontoblast-like morphology and expressed a higher level of DSPP and osteocalcin transcripts than ADH-DPSCs. Conclusion: Collectively, these data indicate that human DPSCs can be expanded and cultured in serum-free supplemented medium with EGF and bFGF. ADH-DPSCs and non-ADH populations contained neuronal and/or oligodendrocyte progenitors at different stages of commitment and, interestingly, cells from spheroid structures seem to be more engaged into the odontoblastic lineage than the ADH-DPSCs.